Necessity of Sinus Lift Surgery in Treatment of Posterior Maxilla with Dental Implants - D. Kopecká; A. Šimůnek; T. Brázda; R. V. Somanathan (Czech Dental Chamber, 2006)
Necessity of the sinus lift procedure in individual locations on the lateral aspect of the maxilla was investigated. The vertical extent of the bone in a position of missed canine, both premolars and first and second molars was measured. The minimum required bone measurement was related to two limit values 12 and 10 mm respectively and all the values obtained were compared with the relevant one. It was found that adequate amount of bone was almost always present in the canine region. In the position of the first premolar, a sinus lift was required in a half and one quarter of the patients, respectively. Three quarters and a half of the patiens, respectively, needed it in the second premolar region. In the molar region, a sinus lift was mandatory in almost all the patients before implantation.